Role of TLR4 in Persistent Leptospira interrogans Infection: A Comparative In Vivo Study in Mice - Nair, Nisha; Guedes, Mariana S.; Hajjar, Adeline M.; Werts, Catherine; Gomes-Solecki, Maria (Frontiers in Immunology, 2021)
Toll-Like Receptor (TLR) 4, the LPS receptor, plays a central role in the control of leptospirosis and the absence of TLR4 results in lethal infection in mice. Because human TLR4 does not sense the atypical leptospiral-LPS, we hypothesized that TLR4/MD-2 humanized transgenic mice (huTLR4) may be more susceptible to leptospirosis than wild-type mice, and thus may constitute a model of acute human leptospirosis. Therefore, we infected huTLR4 mice, which express human TLR4 but not murine TLR4, with a high but sublethal dose of L. interrogans serovar Copenhageni FioCruz (Leptospira) in comparison to C57BL/6J wildtype (WT) and, as a control, a congenic strain in which the tlr4 coding sequences are deleted (muTLR4Lps-del). We show that the huTLR4 gene is fully functional in the murine background. We found that dissemination of Leptospira in blood, shedding in urine, colonization of the kidney, and overall kinetics of leptospirosis progression is equivalent between WT and huTLR4 C57BL/6J mice. Furthermore, inflammation of the kidney appeared to be subdued in huTLR4 compared to WT mice in that we observed less infiltrates of mononuclear lymphocytes, less innate immune markers and no relevant differences in fibrosis markers. Contrary to our hypothesis, huTLR4 mice showed less inflammation and kidney pathology, and are not more susceptible to leptospirosis than WT mice. This study is significant as it indicates that one intact TLR4 gene, be it mouse or human, is necessary to control acute leptospirosis.